A high‐efficiency mobile phone antenna with a narrow ground clearance reducing the effect of head and hand. Issue 12 (15th September 2021) - Fang, Yixiang; Liu, Ying; Jia, Yongtao; Zhang, Huanhuan; Yu, Guoguo; Wang, Shang
Abstract: A high‐efficiency mobile phone antenna covering GSM band (880–960 MHz), DCS1800, PCS1900, UMTS, LTE2300 and LTE2500 band (1710–2690 MHz) with a narrow ground clearance of 2 mm is proposed considering the effect of head and hand of human. Such antenna for metal‐rimmed smartphone applications is to address the performance deterioration caused by the users. It is found that a high efficiency can be obtained by making the main beam of the antenna not point to the head and hand because less energy is absorbed by human tissue in this case. Theory of characteristic mode (TCM) is applied to guide the design of the higher band (HB) antenna to obtain the desired radiation pattern. The simulated results, which strictly refer to the Cellular Telecommunications Industry Association (CTIA) standard, show that the average efficiency with considering the effect of head and hand (ECEHH) of the designed antenna is improved by 9%, compared to the contrast antenna. A prototype of the proposed antenna is fabricated and measured. The simulated and measured results are in good agreement, which proves that the proposed antenna has a high ECEHH in the HB.